Synthesis, Characterization and Study of Mesomorphic Behavior of New Bent and Liner Core Compounds Containing Heterocyclic - Karam, Nisreen H.; Shanshal, Alaa K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
We described herein the synthesized and characterized of new bent and liner core compounds containing thiazolidin-4-one ring[XI-XIII] and [XIV-XVI] respectively. These compounds synthesized by sequence reactions starting from reaction resorcinol or hydroquinone with chloracetyl chloride to yield compounds [I] and [II] ,then the later compounds reactant with 4-hydroxybenzylaldehyde to product dialdehyde compounds [III] and [IV] .The Schiff bases compounds[V-VII] and [VIII-X] synthesized from reaction the compound [III] or [IV] with different aromatic  amines, while the bent and liner core mesogens containing thiazolidin-4-one ring [XI-XIII] and [XIV-XVI] synthesized from reaction Schiff bases compounds[V-VII] or  [VIII-X] with thioglycolic acid. In addition estrfecation of cinnamic acid with methanol to yield ester compound[XVII]which was converted to their acid hydrazid[XVIII] and the acid hydrazid reacted with glysine in phosphorous oxychloride to yield (5-styryl-1,3,4-oxadiazol-2-yl) methanamine [XIX]. Then reactant the1,3,4-oxadiazol compound[XIX]    with dialdehyde compound [III] or  [IV] to product new Schiff bases compounds [XX] and [XXI]  , afterword added thioglycolic acid to give new thiazolidin-4-one derivatives [XXII] and [XXIII], respectively.        The synthesized compounds were characterized by melting points , FTIR ,1HNMR and mass spectroscopy (of some of them).The liquid crystalline properties were studied by hot stage polarized optical microscopy (POM) and differential scanning calorimetry(DSC).All the  Schiff bases compounds [V-X] showed liquid crystals phases while thiazolidin-4-one derivatives[XI-XIII],[XIV-XVI]and [XXIII] didnâ€™t show any liquid crystals properties except the compound [XXII] showed enantiotropic nematic phase.